Lifestyle Medicine-Related Cardiovascular Risk Factor Changes in Employees Participating in a Pharmacist-Run Risk Reduction Program - Thomas L. Lenz; Nicole D. Gillespie; Michele A. Faulkner; Maryann Z. Skrabal; Jessica J. Skradski; Yongyue Qi; Jessica C. Larson (University of Minnesota Libraries Publishing, 2012)
Cardiovascular disease (CVD) remains the leading cause of death among American adults accounting for approximately one-third of all deaths. It has been shown, however, that the actual causes of death are related to lifestyle behaviors such as tobacco use, poor diet and physical activity and alcohol consumption. A pharmacist-run employee health program, started in 2008, sought to lower CVD risk through the use of individualized lifestyle behavior programming, medication therapy management, and care coordination activities. Following one year of participation in the program, employee participants were shown to significantly increase exercise quantity (p < 0.001), fruit and vegetable consumption (p < 0.001), and decrease self-reported stress level (p = 0.006). The percentage of program participants simultaneously adherent to the recommended levels of exercise, combined fruit and vegetable intake and tobacco abstinence at one-year was 34.5% vs. 5.5% at baseline. This compares with only 5.1% of the U.S. population adherent to the same three behaviors. Pharmacists can positively impact healthy lifestyle behaviors when working in an employee health setting.   Type: Original Research